Idee mesjańskie w Prawosławiu. Mesjanizm w testamencie św. księcia Łazarza - Ławreszuk, Marek (Elpis, 2014)
In this text we will try to discuss the concept of the messianistic ideas in Orthodoxy. Among the existing ideas, we will focus our attention on the ideas associated with the testament of Saint Prince Lazarus. The present text will allow us to note the similarities connecting Kosovo testament with the Messianic ideas, and shows the significant differences between them. The text will show Kosovo testament in the spirit of Orthodox theology and spirituality. Teaching, which gave Saint Prince Lazarus is an example of Christian spirituality that goes beyond the temporality and carries moral values based on the Holy Gospel and Holy Tradition.